EVALUASI BIAYA DIFERENSIAL DALAM PENGAMBILAN KEPUTUSAN MENERIMA ATAU MENOLAK PESANAN KHUSUS PADA UD.KAREMA - Mangare, Rivo Jeaner; Morasa, Jenny; Pinatik, Sherly (GOING CONCERN : JURNAL RISET AKUNTANSI, 2016)
The economic growth in Indonesia is rapidly increasing, making businesses in Indonesia to grow faster and move forward. It is demanding textile industries in order to produce quality products and in accordance with the development of the fashion world continues to grow. This study aims to describe the differential cost evaluation in the decision to accept or reject the special order on the company UD.Karema. Type of research method used is quantitative descriptive with case study approach. Location of research conducted at UD.Karema.. Results from this study are: the company will earn a profit contribution of Rp.19.547.917 if accept the special orders. According to research, company must accept special orders for the profit contribution. UD.Karema leaders should apply the differential cost calculation for making decisions to accept or reject special order.